Perancangan Playbook Identifikasi Serangga Sebagai Bahan Penunjang Pembelajaran IPA di Bakal Sekolah Alam Kampung Wisata Isyo Hills Rhepang Muaif, Nimbokrang, Kabupaten Jayapura - Evie L. Warikar; Euniche R.P.F. Ramandey; Henderina J. Keiluhu (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
The purpose of this activity is to design an insect identification playbook and introduce and directly practice insect identification through this playbook to teachers and elementary school students at Sekolah Alam